Early voting in Australia: the costs and benefits of convenience. (4th May 2018) - Sheppard, Jill; Beauregard, Katrine
ABSTRACT: Pre-election day voting increases the opportunities for citizens to vote in an election. This paper asks who votes before election day in Australia and whether early voters and election day voters decide their vote differently. In Australia's compulsory voting system early voting lowers the costs of voting for citizens who would otherwise be compelled to vote on a prescribed day. We may therefore expect that in a compulsory system, early voting has the effect of bringing forward some voter turnout, while aggregate turnout is unaffected. Using 2016 Australian Election Study data, we find that early voters do not appear to suffer time constraints distinguishing them from election day voters: they are no more likely to have caring responsibilities nor to work in time-inflexible occupations. Early voters tend to be older than election day voters, and are more likely to strongly dislike the leader of their non- preferred party. However, feelings towards the parties generally and the state of the economy are not related to early voting. This research suggests that of expanding the voting period in compulsory systems provides greater voter convenience but reduces the capacity of campaign promises and events to affect vote choice.